Implementasi Kode Etik Pustakawan di Perpustakaan Umum dan Arsip Daerah Kota Malang - Putra, Dedy Dwi (Jurnal Administrasi Publik, 2015)
Abstract: The Implementation of Indonesian Librarian Code of Ethics in Regional Public Library and Archives Malang. Librarian as a profession has responsibility to conduct his/her profession tasks based on ethic standard such as shown in Indonesian Librarian Code of Ethics. Librarian in Regional Public Library and Archives Malang is a group of Indonesian librarian who has responsibility to conduct Indonesian Librarian Code of  Ethics. This study aimed to describe the implementation of librarian code of ethics in Regional Public  Library and Archives Malang and related aspects inside it; they are knowledge, understanding, and comprehension of librarian toward Indonesian librarian code  of ethics also infrastructure of public ethic in supporting the implementation. Result of this study shows that librarian have known, understood, and comprehended Indonesian librarian code of  ethics. The implementation of Indonesian Librarian Code of Ethics has not all implemented by the librarian. The constraints in implementing librarian code ethics are the less effort or action on the implementation conducted by librarian also the less active participation from regional IPI management. Therefore, to optimize the implementation of librarian code of ethics, there is needed active role from IPI especially in regional, and evaluation program for ethic in office environment also it is needed to conduct routinely to maximize the role of ethic infrastructure in supporting the implementation code of ethics.   Keywords: implementation, librarian, librarian code of ethics   Abstrak: Implementasi Kode Etik Pustakawan Indonesia di Perpustakaan Umum dan Arsip Daerah Kota Malang. Pustakawan sebagai seorang profesi memiliki tanggung jawab untuk melaksanakan tugas profesinya berdasarkan pada standar etika, seperti yang tercermin dalam Kode Etik Pustakawan Indonesia. Penelitian ini bertujuan untuk mendeskripsikan implementasi kode etik pustakawan di Perpustakaan Umum dan Arsip Daerah Malang, dan aspek yang berkaitan didalamnya yaitu pengetahuan, pengertian, dan pemahaman pustakawan terhadap kode etik pustakawan Indonesia, serta infrastruktur etika publik dalam mendukung implementasi. Hasil penelitian menunjukkan bahwa pustakawan telah mengetahui, mengerti, dan memahami kode etik pustakawan Indonesia, akan tetapi belum sepenuhnya dijalankan oleh pustakawan. Kendala dalam implementasi kode etik pustakawan adalah kurangnya upaya atau tindakan implementasi dari pustakawan, serta kurangnya keaktifan dan kontrol dari pengurus IPI daerah. Oleh karena itu, untuk mengoptimalkan implementasi kode etik pustakawan, perlu adanya peran aktif dari IPI khususnya tingkat daerah, dan program evaluasi etika di lingkungan kantor juga perlu dilaksanakan secara berkala, serta memaksimalkan peran infrastruktur etika dalam menunjang pelaksanaan kode etik.   Kata kunci: implementasi, pustakawan, kode etik pustakawan